A Retrospective Review of Revision and Re-revision Patella Osteosynthesis Performed for Failure of Fixation of Initial Comminuted Fracture Patterns: Very High Complication Rates - Hoskins, Wayne; Gusho, Charles; Parola, Rown; DeFroda, Steven; Haase, Douglas (The Journal of Knee Surgery, 2024)
Literature on revision osteosynthesis for failed patella fracture fixation is extremely limited. This study reviews the treatment options and outcomes for revision and re-revision osteosynthesis at a Level 1 trauma center. All patella revision osteosynthesis cases between January 2021 and March 2024 were identified using Current Procedural Terminology codes at a single tertiary care academic center. Medical records, operative reports, and radiographs were reviewed to collect details regarding patient demographics, initial injury and fracture management, indications for revision surgery, revision construct, postoperative weight bearing and range-of-motion restrictions, and outcomes. The primary outcome was major failure defined as loss of fixation or further surgery for nonunion or infection. Ten patients underwent revision osteosynthesis for failed fixation. All fractures were initially comminuted fracture patterns (AO/OTA 34-C3), with nine (90%) initially treated with a 2.7-mm patella-specific variable angle locking plate (Synthes, Paoli, PA). Half (n = 5) of the patients were revised with the same patella-specific plate and half with an all suture transosseous fibertape tension band (Arthrex, Naples, FL). Additional fixation in the form of bony augmentation was performed in 20% (n = 2) of cases and soft tissue augmentation in 70% (n = 7). There was a 70% (n = 7) major failure rate, mostly due to loss of inferior pole fixation. There were four re-revision procedures performed with surgical fixation. Two of these subsequently developed infection, one united and the other had no radiographic signs of union and was lost to follow-up, but was without complication. Regardless of the chosen fixation construct, revision osteosynthesis for failed fixation of initial comminuted fracture patterns has an extremely high rate of failure. Complications increase with further revision surgery. Level of evidence: therapeutic level 3.
Keywords: patella; fracture; knee; comminution; AO/OTA 34-C3